2020
DOI: 10.1177/0733464820975905
|View full text |Cite
|
Sign up to set email alerts
|

Senior Center Service Utilization: Do Social Ties Affect Participation Patterns?

Abstract: Purpose A better understanding of service utilization patterns at senior service centers can improve program development and constituent usage Theory This research examines whether participation in senior center activities is a function of senior socialization that reinforces and supports existing social ties by selecting specific activities in senior centers. Methods A total of 924 participants of senior centers in a municipality in the Southwest were surveyed. Results We find that having closer friends influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Grandparenting functioning is influenced by a multitude of psychological and environmental factors that will need further analysis. For example, all participants came from community senior centers, in which a positive impact on health and social aspects has been seen previously [75,76]. However, within this group, the study still found differences relating to grandparenting functioning and the impact on participants' wellbeing, depending on parenting during the socialization years.…”
Section: Discussionmentioning
confidence: 99%
“…Grandparenting functioning is influenced by a multitude of psychological and environmental factors that will need further analysis. For example, all participants came from community senior centers, in which a positive impact on health and social aspects has been seen previously [75,76]. However, within this group, the study still found differences relating to grandparenting functioning and the impact on participants' wellbeing, depending on parenting during the socialization years.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited research regarding the racial and ethnic profile of senior center attendees. Among studies that include race and ethnicity, the portion of attendees who are non‐white ranges from 12% to 47% (Aday et al, 2018; Choi, An, & DiNitto, 2020; Keyes et al, 2020; Pardasani 2010; Pardasani & Berkman, 2020). It is not clear, however, how representative of senior center population these figures are.…”
Section: Introductionmentioning
confidence: 99%